Variation among vocalizations of Taraba major (Aves: Thamnophilidae) subspecies - Sementili-Cardoso, Guilherme [UNESP]; Rodrigues, Fernanda Goncalves [UNESP]; Martins, Rafael Martos [UNESP]; Gerotti, Raphael Whitacker [UNESP]; Vianna, Renata Marques [UNESP]; Donatelli, Reginaldo Jose [UNESP] (Taylor & Francis Ltd, 2018)
Geographical variation of bird vocalizations may be related to factors influencing sound production and sound propagation. If birds, e.g. the Great Antshrike (Taraba major), produce vocalizations that develop normally in the absence of learning, these variations may reflect evolutionary divergence within species. In this case, vocal variation could be influenced by habitat structure, since abiotic features and vegetal cover affect sound propagation through environment. Selective pressures may be acting on populations in different ways, which could culminate in a process of speciation. Thus, we searched for structural variation of Great Antshrike vocalizations between subspecies and sought for relationships between these vocal variation and environmental structure. We found variations in frequency and time features of vocalizations among subspecies, which are correlated to latitude, elevation and climate. We also observed an increase in vocal differences along with an increase in distances between individuals, which could reflect isolation of subspecies and the vocal adaptation to different environments.
Keywords: Suboscine; isolation-by-distance; vocal variation; bioacoustics; acoustic adaptation